Mathematical modeling of the effect of temperature on the activity and thermal stability of the inulinase of Kluyveromyces marxianus NRRL Y-7571 - Diestra, Jesús (2015)
A mathematical model was used in this study to describe the effect of temperature on the activity and thermal stability (non-reactive conditions) of the inulinase of Kluyveromyces marxianus NRRL Y-7571. The model was taken from the literature, which was developed using the Arrhenius equation and experimental data. A first-order kinetic equation was takenfor enzyme inactivation. The model parameters were determined by linear and nonlinear regression, reporting confidence intervals. The experimental data showed that the maximum activity acting on sucrose and inulin was reached at 55 °C and that these activities were highly sensitive to higher temperatures. Furthermore, inulolytica activity was more thermally stable than the invertase activity in the range from 48 to 60 °C. Using the model, the process temperature for the hydrolysis of sucrose and inulin was determined at the intersection of the curves of the relative activity and relative half-life, resulting 49 °C for both processes. Although this model was used with reference to the sucrose and inulin hydrolysis, the approach is a useful tool that can be applied to other enzymatic processes for determining the operating temperature, which is ultimately determined by an economic evaluation.